2015
DOI: 10.5455/jib.20150715120224
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and anti-nutritional composition of Lantana camara leaf

Abstract: Objectives: The nutritional and anti-nutritional contents of Lantana camara leaf were investigated. Levels of nutrients like the crude protein, crude fat, crude fibre, ash, mineral and anti-nutrients like phytate, tannins and oxalate were determined. Methods: The nutritional and anti-nutritional contents of L. camara leaf were investigated using standard methods. Results: The results of the proximate analysis showed that the crude protein content was the highest among other components with the value of 24.84±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…Sodium, potassium, calcium, and magnesium are macrominerals, whereas iron, zinc, copper, manganese, cobalt and nickel are micro-minerals which are also known as trace elements. The trace elements are required in very trace quantities as they are important for the physiological and biological functions of the human body [41,42]. These elements can sometimes act as antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium, potassium, calcium, and magnesium are macrominerals, whereas iron, zinc, copper, manganese, cobalt and nickel are micro-minerals which are also known as trace elements. The trace elements are required in very trace quantities as they are important for the physiological and biological functions of the human body [41,42]. These elements can sometimes act as antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reasons have been put forward to explain why L. camara has been particularly successful as an invasive species [ 37 ]. The high tannin content protecting the species from being browsed [ 32 , 33 ], its ability to disperse using birds as vectors [ 51 ] (as well as endozoochory by other animals consuming its drupes [ 54 ]), and its general tolerance to a wide range of ecological factors in anthropogenically disturbed habitats appear to be prime reasons for the species’ high invasion potential [ 34 , 35 , 36 , 57 , 58 , 59 ]. Moreover, it was reported that the digging activity of ungulates, such as pigs, enhances the dispersal of L. camara in Australia by causing the death of trees and subsequent increased light penetration, which favored the spread of Lantana [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although their high tannin content is suspected to largely protect L. camara and C. nardus from being eaten [ 32 , 33 , 42 , 44 , 46 ], it can be assumed than at least some wildlife species (browsing ungulates and primates) consume parts of these plants and thus contribute to their dispersal. Wildlife densities were estimated using the local ecological knowledge of the resident pastoralist population following previously established methods [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations